Stocker Steer Gains and Fly Numbers as Impacted by Burn Date and Type of Mineral on Tallgrass Native Range - J. K. Farney; M. E. Reeb (Kansas Agricultural Experiment Station Research Reports, 2021)
This study aims to evaluate effectiveness of two operational management systems for steer gains and fly control. The first strategy evaluated was pasture burn date of March (MAR) or April (APR). The second management strategy was free-choice mineral with spices (SPICE) or without spices (CON). Eight pastures (n = 281 steers; initial weight 612 ± 57 lb) were used in a 2 × 2 factorial treatment structure. Steers were weighed individually, randomly assigned to treatment, and grazed for 85 days. Weekly, 33% of steers were photographed to count flies and evaluated for hair coat score. Cattle on the APR-SPICE treatment had a greater average daily gain (ADG) than MAR-SPICE and APR-CON with MAR-CON intermediate. Cattle on SPICE were 10 lb heavier than cattle consuming CON mineral. In general, APR-SPICE steers had a greater number of flies on weeks 8, 10, and 11, corresponding to a time when mineral intake averaged 72% of the formulated intake. Additionally, steers on SPICE had a greater number of flies than CON steers. In year 2 of 4 for this study, there was minimal difference in gain based on burn date, primarily because burn dates were only 12 days apart. The use of spices increased weight in cattle but resulted in more flies than control steers. The addition of these spices added $0.02/hd/day to cost of production and the improved gains resulted in a positive return on investment.
Keywords: essential oils; average daily gain; smoke management